Diffraction correction of frequency response for loudspeaker in rectangular baffle - Dobrucki, A. (Archives of Acoustics, 2006)
The problem of diffraction correction of frequency response of loudspeaker in finite baffle was considered by H. Olson [2] in thirties of XX century. He found experimentally the frequency responses of corrections caused by interference of direct and diffracted waves. He predicted necessity of eccentric placing of loudspeaker in the baffle in order to avoid a deep dip in frequency response for frequency higher as twice as for lower limiting frequency of the baffle. However, the problem was never solved theoretically except the simplified case of loudspeaker centrally placed in circular baffle. In the paper a theory of diffraction on the baffle edge of the wave radiated by a point source eccentrically placed in the rectangular baffle is presented. The results of calculations of the diffraction corrections for various configurations of the source and the baffle are presented as well. The statistical dependence between irregularity of the frequency response of the diffraction correction above the lower limiting frequency of the baffle and standard deviation of the diffraction path is shown. The conclusions can be useful for design process of the baffles.